2020
DOI: 10.21203/rs.2.13113/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Predictive models and under-five mortality determinants in Ethiopia: evidence from the 2016 Ethiopian Demographic and Health Survey

Abstract: Background: There is a dearth of literature on predictive models estimating under-five mortality risk in Ethiopia. In this study, we develop a spatial map and predictive models to predict the sociodemographic determinants of under-five mortality in Ethiopia. Methods: The study data were drawn from the 2016 Ethiopian Demographic and Health Survey. We used three predictive models to predict under-five mortality within this sample. The three techniques are random forests, logistic regression, and k-nearest neighb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…The results show that children who were not breastfed were at a significantly higher risk of U5M compared to those who were. These results are in agreement with studies done in India, Bangladesh, and Ethiopia [18,33,34]. However, the very high odds ratio should be interpreted with caution because the confidence interval is very wide.…”
Section: Factors Associated With U5m In Sri Lankasupporting
confidence: 91%
See 1 more Smart Citation
“…The results show that children who were not breastfed were at a significantly higher risk of U5M compared to those who were. These results are in agreement with studies done in India, Bangladesh, and Ethiopia [18,33,34]. However, the very high odds ratio should be interpreted with caution because the confidence interval is very wide.…”
Section: Factors Associated With U5m In Sri Lankasupporting
confidence: 91%
“…A study in Nepal [17] found that children of mothers who did not use contraceptives, did not receive the Tetanus Toxoid (TT) vaccine during pregnancy, and had a previous child death were at higher odds of dying before five years old. A study in Ethiopia [18] found that the income of mothers, source of drinking water, breastfeeding status, type of birth, family size, and birth interval were significant determinants of U5M. Another study in Bangladesh [19] concluded that factors such as contraceptive use by mothers, having other children under 5 years old, previous death of a sibling, birth interval, and birth rank were associated with U5M.…”
Section: Introductionmentioning
confidence: 99%
“…Wealth index was classified as poorer, poorest, middle, richer and richest in EDHS 2016. 23 Maternal educational status was categorised as no formal education, primary, secondary and higher education in our study and by the DHS programme. 24 Data management and model selection Following extraction from the source, data were entered, coded, cleaned, recoded and analysed using Stata V.14.0.…”
Section: Open Accessmentioning
confidence: 99%